Genetically Induced Cholinergic Hyper-Innervation Enhances Taste Learning - Neseliler, Selin; Narayanan, Darshana; Fortis-Santiago, Yaihara; Katz, Donald B.; Birren, Susan J. (Frontiers in Systems Neuroscience, 2011)
Acute inhibition of acetylcholine (ACh) has been shown to impair many forms of simple learning, and notably conditioned taste aversion (CTA). The most adhered-to theory that has emerged as a result of this work—that ACh increases a taste’s perceived novelty, and thereby its associability—would be further strengthened by evidence showing that enhanced cholinergic function improves learning above normal levels. Experimental testing of this corollary hypothesis has been limited, however, by side-effects of pharmacological ACh agonism and by the absence of a model that achieves long-term increases in cholinergic signaling. Here, we present this further test of the ACh hypothesis, making use of mice lacking the p75 pan-neurotrophin receptor gene, which show a resultant over-abundance of cholinergic neurons in subregions of the basal forebrain (BF). We first demonstrate that the p75-/- abnormality directly affects portions of the CTA circuit, locating mouse gustatory cortex (GC) using a functional assay and then using immunohistochemisty to demonstrate cholinergic hyperinnervation of GC in the mutant mice—hyperinnervation that is unaccompanied by changes in cell numbers or compensatory changes in muscarinic receptor densities. We then demonstrate that both p75-/- and wild-type mice learn robust CTAs, which extinguish more slowly in the mutants. Further testing to distinguish effects on learning from alterations in memory retention demonstrate that p75-/- mice do in fact learn stronger CTAs than wild-type mice. These data provide novel evidence for the hypothesis linking ACh and taste learning.